Evaluasi Tingkat Keberhasilan Program Desa Wisata Nongkosawit Kecamatan Gunungpati di Kota Semarang - Deanira Chikita Edelweis; Agung Sugiri (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Tourism activities recently becoming a necessity and a lifestyle of most societies. One of the tourism that is growing quite rapidly is a tourism based on rural areas. The village becomes one of potential resources and has good prospects to develop as it has strong potential to attract tourists, especially for tourists coming from urban areas. Rural-based tourism also plays a role in improving the economy and improving the welfare of the community in the location itself by using the concept of Community Based Tourism (CBT), where local communities also play an active role in the development.Semarang City is one part of the program "Visit Jawa Tengah" which is a leading tourism program for the areas located in the Province of Central Java. Currently the Government of Semarang City is promoting the program "Ayo Wisata ke Semarang!" as a follow-up program of the "Visit Jateng" program. One of the efforts being done is to develop tourist villages in the city of Semarang, one of which is the Nongkosawit Tourism Village located in Gunungpati District. Tourism potential in Nongkosawit Tourism Village is diverse ranging from cattle tours, beautiful rice fields to culinary centers.Seeing the development of Nongkosawit Tourism Village program, then evaluated the program to determine the extent to which the success rate. Research on the evaluation of the Nongkosawit Tourism Village program uses a quantitative descriptive analysis with a questionnaire addressed to local communities and tourists. There are three main aspects of evaluation, namely the aspect of tourism potentia, human, (aspect of local people and tourist aspect. The results of the evaluation program, which indicates that according to respondents indicators are still low is the aspect of tourism potential, especially on the tourist accommodation indicators. Overall, these three aspects have fallen into the "high" category or are already quite satisfactory. After obtaining the conclusions from the results of program evaluation, then compiled a recommendation for both parties namely the Government and the local community